1999
DOI: 10.1086/307458
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Space ObservatoryPhotometric Search of Main‐Sequence Stars for Vega‐Type Systems

Abstract: We obtained 3.6È20 km photometry of 38 bright [IRAS km) [ 0.7 Jy] main-sequence stars with F l (12 the Infrared Space Observatory (ISO). Observations were conducted with the ISOPHOT instrument, in the single-pointing photometry mode, through Ðlters at 3.6, 11.5, and 20.0 km. We searched for excess (Vega-type) emission from dust at temperatures K, located at D1È60 AU from the stars. We thus Z100 sampled dust at warm, terrestrial material temperatures and at cool (D100 K) temperatures of possible Kuiper BeltÈt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
2

Year Published

2000
2000
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 22 publications
1
28
2
Order By: Relevance
“…From a survey of 38 main-sequence stars using IRAS and ISOPHOT data Fajardo-Acosta et al (1999) found no star with a significant excess at 12 µm, and a fraction of ∼14% excess stars at 20 µm. It is difficult to interpret this fraction since the ISOPHOT data used in their study were inconclusive, and the 20 µm detections needed confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…From a survey of 38 main-sequence stars using IRAS and ISOPHOT data Fajardo-Acosta et al (1999) found no star with a significant excess at 12 µm, and a fraction of ∼14% excess stars at 20 µm. It is difficult to interpret this fraction since the ISOPHOT data used in their study were inconclusive, and the 20 µm detections needed confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…We compiled a total of 113 Southern Hemisphere Vega-like candidate stars from the literature, based on their infrared or submillimetric excess emission (Backman & Paresce 1993;Sylvester et al 1996;Mannings & Barlow 1998;Fajardo-Acosta et al 1999;Sylvester & Mannings 2000;Habing et al 2001;Laureijs et al 2002;Sheret et al 2004). This compilation also includes G dwarfs with infrared excess recently detected by Spitzer (Beichman et al 2005(Beichman et al , 2006aBryden et al 2006;Su et al 2006;Trilling et al 2008).…”
Section: The Samplementioning
confidence: 99%
“…Using ISOPHOT data from the Infrared Space Observatory (ISO; Kessler et al 1996) Fajardo-Acosta et al (1999 confirmed the infrared excess of HD 110411 and report a tentative detection of HD 192640 (only at 20 µm).…”
Section: Results Of Infrared Measurements From the Literaturementioning
confidence: 99%
“…Furthermore, the ISO satellite brought a flood of new data for group members. Fajardo-Acosta et al (1999) presented data for three λ Bootis stars, namely HD 11413, HD 110411 and HD 192640. In Sect. 2, we summarize the current literature status on the λ Bootis phenomenon focusing especially on circumstellar dust and gas.…”
Section: Introductionmentioning
confidence: 99%